Variability in Fitness Trade-Offs Amongst Coral Juveniles With Mixed Genetic Backgrounds Held in the Wild - Quigley, Kate M.; Marzonie, Magena; Ramsby, Blake; Abrego, David; Milton, Grant; van Oppen, Madeleine J. H.; Bay, Line K. (Frontiers in Marine Science, 2021)
Novel restoration methods are currently under consideration worldwide to help coral reefs recover or become more resilient to higher temperature stress. Critical field-based information concerning the paradigm of “local is best” is lacking for many methods; information which is essential to determine the risk and feasibility associated with restoration. One method involves breeding corals from different reef regions with expected variation in heat tolerance and moving those offspring to new locations to enhance offspring survival; thereby augmenting local stock to enhance survival for anticipated warming. In this study, surviving colonies from the 2016 to 2017 mass bleaching events on the Great Barrier Reef (GBR) were reproductively crossed and they included colonies sourced from northern (three) and central (two) reefs. The gravid colonies of Acropora tenuis were collected across 6° of latitude, and they were spawned to produce a total of 17 purebred and hybrid crosses. Juvenile corals (3,748 individual colonies settled on 1,474 terracotta tiles) were deployed to Davies reef in the central GBR after 4 months of aquarium rearing. Survival, growth, and coral colour (as a proxy for bleaching) were assessed after 0, 91, and 217 days of field deployment. Overall, a high percentage of juveniles (17% ± 2.5 SE) survived relative to expected survival at the final census. Survival was significantly higher for central purebred crosses, hybrid crosses had intermediate survival while northern purebreds had the lowest survival. Colour and growth rates (0.001−0.006 mm2 day–1) were not significantly different amongst central, northern, or hybrid crosses but were of a reverse pattern compared to survival. On average, northern purebred crosses grew the fastest, followed by hybrid crosses, and then central purebred crosses. Modelled growth trajectories suggest that northern purebreds would take 8 years to grow to reproductive size, hybrids would take nine, and central purebreds would require 12. All deployed juvenile corals paled over time in the field although the colour of A. tenuis juveniles did not differ significantly amongst central, northern, or hybrid crosses. Growth and survival trade-off analysis showed that although most crosses did not outperform the native central juveniles, two of the eight hybrid crosses (SBxLS, DRxCU) demonstrated faster time to reproductive age and increased survival. Overall, reduced time to reach reproductive size and minimal trade-offs in at least two of the eight hybrids suggest that these crosses may accelerate and supplement recovery through natural re-seeding of genes sourced from northern reefs.